A review of properties and behaviour of reinforced geopolymer concrete structural elements- A clean technology option for sustainable development. (1st February 2020) - Hassan, Amer; Arif, Mohammed; Shariq, M.
Abstract: The traditional concrete is one of the most energy-intensive construction materials responsible for about 10% of global anthropogenic carbon dioxide emissions. Efforts are being made to develop an alternative binder for concrete. The geopolymer concrete (GPC) has emerged as a promising novel construction material for the production of cement and provides a clean technology option for sustainable development. This paper undertakes a review of the performance behaviour of reinforced geopolymer concrete structural elements and summarises the findings on the mechanical performance of reinforced GPC elements, e.g., columns, beams, and walls. In this review study, the mechanical properties of GPC structural elements have been investigated and compared with that of OPC concrete. The failure mode of GPC structural element has also been reported, and it was almost in the same manner of OPC concrete failure. The potential of GPC with regards to the chemical resistance and heat resistance could be significantly employed in the various industrial constructions such as marine constructions, pavements, and sewage pipes, etc. Moreover, it was observed that GPC could be safely used in structural elements owing to its excellent mechanical properties using provisions of design codes. More experimental studies are required to give a better understanding of the mechanical properties of GPC for its mass utilization in diversified application areas and spread the clean technology option in the construction industry. Graphical abstract: Image 10000